Structural and Catalytic Characterization of TsBGL, a β-Glucosidase From Thermofilum sp. ex4484_79 - Chen, Anke; Wang, Dan; Ji, Rui; Li, Jixi; Gu, Shaohua; Tang, Rong; Ji, Chaoneng (Frontiers in Microbiology, 2021)
Beta-glucosidase (BGL) is an enzyme that catalyzes the hydrolysis of the glycosidic bonds of cellobiose, resulting in the production of glucose, which is an important step for the effective utilization of cellulose. In the present study, a thermostable β-1,4 glucosidase was isolated and purified from the Thermoprotei archaea Thermofilum sp. ex4484_79 and subjected to enzymatic and structural characterization. The purified β-1,4 glucosidase (TsBGL) exhibited maximum activity at 90 °C and pH 5.0, and displayed maximum specific activity of 103.13 U/mg against p-nitrophenyl β-D-glucopyranoside (pNPGlc) and 37.3 U/mg against cellobiose. Furthermore, TsBGL exhibited a relatively high thermostability, retaining 84 % and 47 % of its activity after incubation at 85 °C for 1.5 h, and 90 °C for 1.5 h, respectively. The crystal structure of TsBGL was resolved at a resolution of 2.14 Å, which revealed a classical (α/β)8-barrel catalytic domain. A structural comparison of TsBGL with other homologous proteins revealed that its catalytic sites included Glu210 and Glu414. We provide the molecular structure of TsBGL and the possibility of improving its characteristics for potential applications in industries.